2020
DOI: 10.1080/10454446.2020.1792022
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Processed Organic Foods: The Impact of Promotional Message Framing (Vice Vs. Virtue Advertising) on Perceptions of Healthfulness

Abstract: The study shows that the perceived healthfulness of processed organic foods, compared to their conventional counterparts, can be altered by slight variations in how promotional messages are framed. A sample of US organic shoppers (N = 375) was exposed to advertisements promoting processed organic (and processed conventional) foods by highlighting either virtue or vice aspects of the products. An interaction between the type of processed food (organic, non-organic) and the type of promotional message (vice, vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 96 publications
0
7
0
2
Order By: Relevance
“…Utilitarian and hedonic attributes impact consumer satisfaction, word of mouth and purchase intentions; however, this depends on how the product is designed and appealed to customers. In terms of food, hedonic purchases are made because the food is delicious, whereas utilitarian purchases are made because they are nutritious, healthy and alleviate hunger (Anghelcev et al, 2020). The entomophagy campaign of "Eat Insects [.…”
Section: Gateway Bug To Edible Insect Consumptionmentioning
confidence: 99%
“…Utilitarian and hedonic attributes impact consumer satisfaction, word of mouth and purchase intentions; however, this depends on how the product is designed and appealed to customers. In terms of food, hedonic purchases are made because the food is delicious, whereas utilitarian purchases are made because they are nutritious, healthy and alleviate hunger (Anghelcev et al, 2020). The entomophagy campaign of "Eat Insects [.…”
Section: Gateway Bug To Edible Insect Consumptionmentioning
confidence: 99%
“…Researchers (Anghelcev et al. , 2020; Pew Research Center, 2016; Rana and Paul, 2017) found, people believe that organic foods are healthier than conventional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (Anghelcev et al, 2020;Pew Research Center, 2016;Rana and Paul, 2017) found, people believe that organic foods are healthier than conventional foods. Rosen (2010) reported the organic foods industry promoted its products as nutritionally superior to conventional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Organic appeals advertising refers to message content and information that explain and emphasize organic elements of a product, such as milk ( Yang and Ghose, 2010 ). In particular, organic appeals advertising often indicates that organic milk is naturally produced with rich nutrition, is processed without chemicals, and is healthy and safe for consumers ( Anghelcev et al, 2020 ). By contrast, non-organic appeals advertising does not present and emphasize organic elements of a milk product ( Carfora et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, non-organic appeals advertising does not present and emphasize organic elements of a milk product ( Carfora et al, 2019 ). Organic appeals advertising may be an effective way to provide useful information and knowledge for consumers to understand organic milk products better ( Anghelcev et al, 2020 ). Although several firms have widely used organic appeals advertising to educate and persuade consumers ( Wu et al, 2019 ), the effect of organic appeals advertising on consumers’ motivation and behavior has been unclear and lacks empirical evidence in prior literature.…”
Section: Introductionmentioning
confidence: 99%